ANALISIS KELAYAKAN FINANSIAL USAHA AYAM KAMPUNG DI DISTRIK SEMANGGA KABUPATEN MERAUKE - Ineke Nursih Widyantari (Universitas Musamus, Merauke, Papua, 2015)
The objectives of this research are to determine the costs, revenues, efficiency and profitable of chicken farm in Semangga district-Merauke. This research was conduct on May until June 2014. The participant of this study was chicken farmers who joined the group of Unggas Jaya, all members were 11 farmers. The results showed that the average total cost of chicken farmer was Rp3,695,512.00. The average of revenue was Rp6,000,000.00 and the average of total profit is 2,304,488.00 per production cycle. Meanwhile the profitability is 62% and R/C ratio is 1.62, which means that every total cost will earn revenue of 1.62 times.